Effect of industrial agglomeration on the efficiency of urban productive land allocation: Evidence from China’s nine national-level urban agglomerations - XIE Wandong, TIAN Shuangqing, MA Xianlei, ZHAO Aidong (Ziyuan Kexue, 2024)
[Objective] Industrial agglomeration is the result of coordinated urban division of labor and is an important factor in promoting the high-quality development of urban agglomerations. Analyzing the effect of industrial agglomeration on the efficiency of productive land allocation in cities provides valuable insights for optimizing resource allocation in urban agglomerations. [Methods] Based on urban economic theory, this study first constructed the theoretical framework of “industrial agglomeration-production improvement-land use allocation efficiency” to explain how industrial agglomeration affects land allocation efficiency. Panel data from 128 prefecture-level cities in China’s nine national-level urban agglomerations from 2009 to 2018 were used to calculate the efficiency of productive land allocation using a super slack-based measure of efficiency data envelopment analysis (Super-SBM DEA) model. The empirical analysis examined the relationship between land allocation efficiency and the level of industrial agglomeration, and analyzed the differences and mechanisms of its effects from the perspectives of regional classification effects and industrial agglomeration characteristics. [Results] The study found the following: (1) During the research period, the efficiency of productive land allocation in the urban agglomerations of China showed an evolving trend of increase-decrease-increase, with spatial differences roughly characterized by an upward trend in the eastern and northeastern regions, stable trend in the central region, and downward trend in the western region. (2) The level of industrial agglomeration has a significant positive impact on the improvement of land allocation efficiency for productive use. (3) The promoting effect of industrial agglomeration on land allocation efficiency for productive use diminishes with the increase in economic development level. (4) Diversified industrial agglomeration have a positive promoting effect. [Conclusion] Therefore, optimizing the industrial development pattern of Chinese urban agglomerations requires differentiated policy improvements that align with the characteristics of urban agglomeration development. This includes strengthening the allocation of resources to industrial agglomerations, adjusting resource allocation towards advantageous areas, and innovating regional industrial structures to foster regional cooperation. Strengthening the coordination of regional resource allocation in urban agglomerations and further improving the efficiency of land allocation for productive use will contribute to achieving sustainable social and economic development.